Urban Slum Upgrading Policy In Jakarta (Case Study: Kampung Deret Program Implementation) - Alfian Nurdiansyah (The Indonesian Journal of Planning and Development, 2018)
For several decades, Jakarta has witnessed massive urbanization that leads to urban slum problems. The problems have always been associated with urban kampung, the informal neighborhood which grows and tends to be more impoverished over times. The local government has implemented the Kampung Improvement Program (KIP) to reduce the problems. The program which included sites-and-services program, and resettlement policy was not entirely successful to overcome slum problems. In 2013, the Governor of Jakarta launched Kampung Deret Program (KDP) as an alternative to the on-site slum upgrading policy. However, the KDP was eventually postponed and removed from the local budget plan of Jakarta Province in 2015 due to some problems in the implementation. This article is aimed at explaining the effectiveness of the KDP program and analyzing alternative strategies for effective policy implementation of KDP. This study uses quantitative methods by applying observation, interview and documentation to collect the primary and secondary data. Petogogan and Pasar Minggu in South Jakarta were selected as cases. The study shows that there are technical difficulties faced by the authorities during the implementation of KDP. KDP Petogogan was quite successful comparing to the KDP Pasar Minggu in terms of installed housing, basic infrastructures-facilities, and security of tenure. The implementation was quite successful due to the application of some form of equal approaches which were based on the characteristic of policy object and the slum dwellers in every selected slum. Following the approach, KDP was implemented under three packages: KDP I, KDP II, and KDP III. It was finally found that the KDP packages were considered as an effective on-site slum upgrading policy that can minimize resistance and maximize participation from the slum dwellers.